Metabolic and physiological changes during and after vaquejada exercise in horses - Hunka, Monica Miranda; Souza, Luzilene Araújo; Almeida, Thaís Helena Sougey de; Nery, Priscilla Cristina Rolim; Manso, Helena Emília Cavalcanti da Costa Cordeiro; Filho, Hélio Cordeiro Manso (Medicina Veterinária, 2019)
Physiological and metabolic evaluations of equine sports have been conducted to define parameters or biomarkers for performance evaluation, clinical diagnosis and predict fatigue and overtraining. Actually, the vaquejada is the most important equine sport in Brazil, and these horses are repeatedly submitted to shortduration physical exertion, during 2 or 3 alternate or consecutive days, requiring adequate conditioning for this equestrian modality. The objective of this study was to test the hypothesis that pulls horses and helper horses undergo physiological and metabolic changes during vaquejada races. Eighteen Quarter Horses were used, including 12 pull horses and 6 helper horses. Hemograms and the following analyses were performed: glucose, lactate, cholesterol, triglycerides, NEFA, total proteins, albumin, creatine kinase, gama glutamyl transferase and cortisol. A heart rate monitor was used to measure the heart rate, velocity and travel distance of each animal. Statistical analyses were performed using ANOVA and Tukey's tests, with P established at 5%. Pull horses had higher heart rate values, but the velocities attained by the two groups of horses were similar. There was an increase in heart rate, glucose, lactate, non-esterified fatty acids and cortisol in both pull and helper horses after racing, but these levels returned to resting values 30 minutes after the end of exercise. It was concluded that the vaquejada field test promoted significant changes in haematological, biochemical biomarkers and in the heart rate of both groups of horses.